Economic Burden and Epidemiology of Pneumonia in Korean Adults Aged over 50 Years - Yoo, Kwang Ha; Yoo, Chul Gyu; Kim, Se Kyu; Jung, Ji Ye; Lee, Myung Goo; Uh, Soo Taek; Shim, Tae Sun; Jeon, Kyeongman; Shim, Jae Jeong; Lee, Heung Bum; Chung, Chi Ryang; Kang, Kyung Woo; et al. (Journal of Korean medical science, 2013)
This study was performed to estimate the direct medical costs and epidemiology of pneumonia in adults of Korea. We conducted a multi-center, retrospective, observational study and collected data targeting for community-acquired pneumonia patients ( ≥ 50 yr) from 11 hospitals. Costs attributable to the treatment of pneumonia were estimated by reviewing resource utilization and epidemiology data (distribution of pathogen, hospital length of stay, overall outcome) were also collected. A total 693 patients were included; average 70.1 ( ± 10.5) aged, 57.3% male and average 1.16 CURB-65 (confusion, blood urea nitrogen, respiratory rate, blood pressure, age > 65 yr) scored. The pathogen was identified in the 32.9% (228 patients); Streptococcus pneumoniae accounted for 22.4% (51 patients) of identified pathogens. The hospital mortality was 3.2% (especially, for S. pneumoniae was 5.9%) and average length of stay was 9 days. The mean total cost for the treatment of pneumonia was US dollar (USD) 1,782 (SD: USD 1,501). Compared to the cost of all caused pneumonia, that of pneumococcal pneumonia was higher, USD 2,049 ( ± USD 1,919), but not statistically significant. Charge of hospitalization accounted the greatest part of total medical costs. The economic burden of pneumonia was high in Korea, and the prevention of pneumonia should be considered as effective strategy.